Efektivitas Pelatihan Forward lunges dalam Meningkatkan Kekuatan Otot Tungkai pada Atlet Kabaddi - Rizky Hadinata Zulfani; Suratmin Suratmin; I Ketut Iwan Swadesi (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2026)
This study aimed to analyze the effect of forward lunges training on improving the leg muscle strength of kabaddi athletes. The study employed a quasi-experimental method with a pretest-posttest control group design. The sample consisted of 34 male Kabaddi athletes from Klungkung Regency who met the inclusion and exclusion criteria, selected using total sampling and then randomly allocated into treatment and control groups. Leg muscle strength was measured using a leg dynamometer during the pretest and posttest after a six-week training program. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, Levene’s homogeneity test, paired t-test, and independent t-test. The results showed that the mean leg muscle strength in the treatment group increased from 93.35 ± 4.996 kg to 150.41 ± 16.111 kg, whereas the control group increased from 95.45 ± 3.931 kg to 101.37 ± 5.483 kg. The percentage increase in the treatment group was 61.12%, higher than the 6.20% increase in the control group. The independent t-test on posttest scores showed a significant difference between groups (p < 0.001). Therefore, forward lunges training was effective in improving the leg muscle strength of kabaddi athletes.